2021
DOI: 10.3389/fcell.2021.641404
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Is Deranged in Asthmatic Bronchial Epithelium and Fibroblasts

Abstract: Both canonical and non-canonical Wnt signaling pathway alterations have been documented in pulmonary disease pathogenesis and progression; therefore, they can be an attractive target for pharmaceutical management of severe asthma. Wnt/β-catenin signaling was shown to link early embryonic lung development impairment to later in life asthmatic airway remodeling. Here we explored the changes in Wnt signaling associated with asthma initiation and progression in epithelial and fibroblasts using a comprehensive appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…A GWAS of asthma symptoms in 1,246 children in the population of Salvador, Brazil, was carried out ( Costa et al, 2015 ); they found that BCL11A is associated with hematopoietic symptoms of asthma, and it may be related to its interaction with BCL 6 and participation in hematopoietic cell differentiation. In addition, in another study of severe asthma ( Hachim et al, 2021 ), they found that BCL11A was downregulated. MATK (megakaryocyte-associated tyrosine kinase) is a protein-coding gene too.…”
Section: Discussionmentioning
confidence: 97%
“…A GWAS of asthma symptoms in 1,246 children in the population of Salvador, Brazil, was carried out ( Costa et al, 2015 ); they found that BCL11A is associated with hematopoietic symptoms of asthma, and it may be related to its interaction with BCL 6 and participation in hematopoietic cell differentiation. In addition, in another study of severe asthma ( Hachim et al, 2021 ), they found that BCL11A was downregulated. MATK (megakaryocyte-associated tyrosine kinase) is a protein-coding gene too.…”
Section: Discussionmentioning
confidence: 97%
“…There is a deranged balance between Wnt enhancer and Wnt inhibitors in the bronchial epithelium of severe asthmatic patients. The Th2-high asthma phenotype is associated with upregulated Wnt-negative regulators, while higher canonical Wnt signaling enriched pathway are observed in both inflammatory and severe neutrophilic asthmatics 53 .…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, treatment with the corticosteroid dexamethasone reduced inflammation and remodeling in wild-type but not club cell-specific ITGB4 knockout mice [ 64 ]. While the airway epithelial SASP is not defined for asthma, recent studies reported altered WNT/β-Catenin signaling between bronchial epithelium and fibroblasts that increased fibroblast senescence and airway remodeling [ 65 ]. These data suggest that aging may negatively impact the airway epithelium and disruption to changes to adhesion and barrier integrity can promote senescence and persistent airway remodeling in asthma.…”
Section: Aging-related Mechanisms In Asthmamentioning
confidence: 99%